Public finance indicators and the value of investment project development: a comparative study of GCC countries - Alshubiri, Faris Nasif (Journal of Business Economics and Management, 2019)
This study aims to identify public financial indicators involved in the investment projects of GCC countries. The data was collected from the IMF and the MEED from 2011-2017. The study measured the impact of public finance based on eight variables and two proxies (national and trade accounts) on the investment project development proxy, which is measured by the total value of projects planned or currently underway and the value of the ten largest projects currently underway. The results showed that Saudi Arabia and the UAE rank high in both proxies of investment project development. The simple regression results also illustrated that real GDP, the real non-oil GDP variables of national account proxy, and the value of the exported goods and services variable of the trade accounts proxy have a significant impact on the total value of projects planned or currently underway. Meanwhile, only three factors of national accounts, gross national savings, CPI inflation, and current account balance, have a significant impact on the value of the ten largest projects currently underway. The overall conclusion of the study is that GCC countries have established high-value development projects in different cities that require a proper public policy to efficiently manage capital expenditure within the public sector.